Commentary on the Old Testament ; v. 6 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Easton, M.G. (Grand Rapids, MI Eerdmans)
Contents : v. 6 : Proverbs, Ecclesiastes, Song of Solomon / F. Delitzsch. Includes bibliographical references.
Reprinted 1973.
Keywords: Bible. O.T. -- commentaries